Human Trafficking Interventions (HTI): A Rapid Documentary Analysis of Central Asia Region’s (CAR) Efforts - Daniel Esson; Vera Ansie; Theresa Ameke (Ilomata International Journal of Social Science, 2023)
The governments in the Central Asian Region (CAR), until recently, have failed to recognize the prevalence of human trafficking as a social and human rights problem. Even though the problem has persisted for a long time, there is almost non-existent empirical evidence on intervention approaches. Therefore, this study curates and synthesizes evidence on human trafficking interventions in CAR to open up academic conversations in this area. This study adopts the rapid documentary analysis approach as a starting point for further studies, drawing insights from the ecological systems theory to examine human trafficking interventions in CAR. The data is analyzed in line with thematic analysis procedures. Major themes representing overarching mechanisms used in the CAR to intervene in human trafficking situations include 1) awareness creation to expand knowledge on human trafficking 2) provision of shelter and psychosocial support 3) collaborations between different organizations and sectors and 4) tightening legislation. The findings suggest that while this study sets to open conversations about human trafficking interventions in Central Asia as the first study on human trafficking interventions, it is important to use other data curation methods to explore the extent of human trafficking interventions in the region which will fill any information gap this study might have missed.